Cross-resistance to pyrethroids and neonicotinoids in malaria vectors from vegetable farms in the Northern Benin - Boukari, M.K.Y.; Djegbe, I.; Tepa-Yotto, G.; Hessou-Djossou, D.; Tchigossou, G .; Tossou, E.; Lontsi-Demano, M.; Adanzounon, D.; Gbankoto, A.; Djogbenou, S.L.; Djouaka, R.F. (MDPI, 2024)
Agricultural pesticides may play a crucial role in the selection of resistance in field populations of mosquito vectors. This study aimed to determine the susceptibility level of An. gambiae s.l. to pyrethroids and neonicotinoids in vegetable farms in northern Benin, in West Africa, and the underlying insecticide resistance mechanisms. A survey on agricultural practices was carried out on 85 market gardeners chosen randomly in Malanville and Parakou. Anopheles gambiae s.l. larvae were collected, reared to adult stages, and identified to species level. Susceptibility was tested with impregnated papers (WHO bioassays) or CDC bottles according to the insecticides. Synergists (PBO, DEM, and DEF) were used to screen resistance mechanisms. Allelic frequencies of the kdr (L1014F), kdr (L1014S), N1575Y, and ace-1R G119S mutations were determined in mosquitoes using Taqman PCR. Fertilizers and pesticides were the agrochemicals most used with a rate of 97.78% and 100%, respectively, in Malanville and Parakou. Anopheles coluzzii was the predominant species in Malanville, while An. gambiae was the only species found in Parakou. Bioassays revealed a high resistance of An. gambiae s.l. to pyrethroids and DDT, while a susceptibility to bendiocarb, pyrimiphos-methyl, malathion, and clothianidin was recorded. Resistance to acetamiprid was suspected in mosquitoes from both localities. A lower resistance level was observed when mosquitoes were pre-treated with synergists, then exposed to insecticides. The kdr L1014F mutation was observed in both locations at moderate frequencies (0.50 in Malanville and 0.55 in Parakou). The allelic frequencies of N1575Y and G119S were low in both study sites. This study confirmed the resistance of An. gambiae s.l. to insecticides used in agriculture and public health. It reveals a susceptibility of vectors to bendiocarb, pyrimiphos-methyl, malathion, and clothianidin, thus indicating that these insecticides can be used as an alternative in Benin to control malaria vectors.